Modelagem e implementação de um sistema de processamento digital de sinais baseado em FPGA para geração de imagens por ultrassom usando Simulink - Ferreira, Breno Mendes (2017)
Ultrasound (US) is a well-established technique that has been widely used for testing, characterizing and visualizing internal structures of biological and non-biological material. The US research group of the Federal University of Technology - Paraná developed the ULTRA-ORS system, which, although suitable for research related to multichannel excitation and reception, uses a large computing time, due to the personal computer processing. This research presents the modeling, implementation and validation of a digital processing system of signals based on a FPGA (Field-Programmable Gate Array) device of high performance for the reconstruction of images through US, using the beamforming technique. The software Simulink and the tool DSP Builder were used for simulation and transformation of the following models in hardware description language: digital filter FIR (Finite Impulse Response), CIC (Cascaded Integrator-Comb) Interpolation filter, variable delay, apodization, coherent summation, decimation, demodulation with envelope detection and logarithmic compression. After the Simulink validation, the design was synthesized for a Stratix IV FPGA and implemented on the Terasic DE4-230 board. The tool SignalTap II in the software Quartus II was used to acquire the processed signals from the FPGA. For the graphic and quantitative evaluation of the accuracy of this method, we used real raw US data, acquired from the ULTRA-ORS with sampling frequency of 40 MHz and 12-bit resolution, and the normalized root mean squared error (NRMSE) in comparison with the same functions implemented through scripts in Matlab. As a main result of the modeling, in addition to the individual responses of each implemented block, comparisons between the reconstructed images by ULTRA-ORS and FPGA processing for four apodization windows are presented. The excellent agreement between the simulated and experimental results with NRMSE values lower than 6.2% and total processing latency of 0.83 µs corroborates the simplicity, modularity and effectiveness of the proposed modeling for use in US signal processing research for real-time image reconstruction.